Immunohistochemical localization of endothelial nitric oxide synthase in endometrial tissue of women with unexplained infertility - Tohid Najafi; Marefat Ghaffari Novin; Jalil Pakravesh; Khadijeh Foghi; Fatemeh Fadayi; Gelareh Rahimi (Iranian Journal of Reproductive Medicine, 2012)
Background: Nitric oxide (NO) is a molecule that incorporates in many physiological processes of female reproductive system. Recent studies suggested the possible role of endothelial isoform of nitric oxide synthase (eNOS) enzyme in female infertility. Objective: The aim of this study is to evaluate the expression of endothelial nitric oxide synthase in endometrial tissue of women with unexplained infertility. Materials and Methods: In this case-control study a total of 18 endometrial tissues obtained from 10 women with unexplained infertility and 8 normal and fertile women by endometrial biopsy, 6 to 10 days after LH surge. Specimens were fixed in 4% paraformaldhyde fixative and frozen sectioned for semi-quantitative immunohistochemical evaluation using monoclonal anti-human eNOS antibody. Hematoxilin and Eosin was used for Histological dating. Results: Localization of endothelial nitric oxide synthase was seen in glandular and luminal epithelium, vascular endothelium and stroma in both fertile women and women with unexplained infertility. Although there were differences in immunoreactivity of glandular epithelium (p=0.44), vascular endothelium (p=0.60) and stroma (p=0.63) but only over-expression of eNOS in luminal epithelium (p=0.045) of women with unexplained infertility compared to fertile women was statistically significant (p<0.05). Conclusion: This study suggests that changes in luminal expression of eNOS may influence receptivity of endometrium